Penerapan Enterprise Resource Planning Pada Sistem Procurement Dan Inventory Toko Loumo Education Yogyakarta - Sepriandi Parningotan (IMTechno: Journal of Industrial Management and Technology, 2021)
Loumo Education is a stationery shop or office stationery that has been established in Yogyakarta since January 2020. From the interviews obtained by the author, there are several obstacles that are experienced, namely in the process of stocking goods or inventory and purchasing or procurement. In the process of inventory and procurement, the running system is still very simple so that there are many problems faced, such as stock calculation errors that result in out of stock but not recorded and can result in delays in purchasing goods, besides that the problem that occurs is the receipt of the number of purchased products does not match the quantity order. There are also other obstacles, namely the loss of inventory and purchase documents, repeated records, and the difficulty in finding the desired data. For that we need an open source software, which can use the Odoo software. In this study, the authors used modules contained in Odoo, namely the procurement and inventory modules. The research method that I use in this research has several stages, namely interviews, problem identification, literature review, system design analysis, and application or implementation. The purpose of this study is to produce a system that can assist in managing data on purchases and supplies at Loumo Education stores. The result of this research is that the application of Odoo modules, namely procurement and inventory, is very suitable and supports the business process of purchasing and supplies at Loumo Education stores.